IMF-Supported Programs: Recent staff research - Mody, Ashoka; Rebucci, Alessandro; International Monetary Fund. (Washington, D.C.: International Monetary Fund, 2006)
A long tradition of research has sought to evaluate the effectiveness of IMF supported programs. This volume includes recent research that moves decisively beyond the typical characterization of programs. First, as the essays in this volume demonstrate, the IMF's advice and financing are conditioned by a variety political economy considerations. International political economy has a bearing on program selection, conditionality, and implementation. Second, the IMF's governance structure also has implications for program design and implementation, and, hence, for the IMF's economic effectiveness.
Includes bibliographical references.
ne 6/05/2018
Ref.
Keywords: Bailouts (Government policy)